Cálculo da luminosidade de raios cósmicos de galáxias Starburst - Mocellin, Adriel Gustavo Bartz (2022)
Ultra-high energy cosmic rays (UHECR) are the most energetic of all subatomic particles ever observed in nature. The search for its mysterious origin is currently a major scientific challenge. Great progress in this direction has been made by the Pierre Auger Observatory, which can measure events above 1 EeV quite accurately. In this work, we investigate the possibility that these particles originate from Starburst Galaxies. However, the study of cosmic rays depends heavily on the study of their propagation in the universe to Earth. In the first part of the paper, we discuss the Hillas criterion for describing possible sources of cosmic rays, the energy spectrum, anisotropy, and composition, and then we address the main energy losses on the way of these particles to Earth. Based on the literature, we analyze the physical processes that can accelerate particles and a possible correlation between cosmic ray arrival directions and Starburst Galaxies. We argue that if Starbursts are possible sources of acceleration, then the acceleration of particles in terminal shock and the formation of winds and bubbles that result are the conceptual model that best describes this process. In the last part, an upper limit on the gamma-ray flux integral is used to obtain the upper limit on the luminosity of UHECR for the Starburst Galaxy Arp 220 and the partial luminosity for other six Starburst sources. This correlation arises from the regime of particle cascades that occur as cosmic rays propagate in radiation fields as they propagate through the universe.